Family-Centred care and the relationship between hospital staff and parents - Shields, Linda (Burapha University, 2010)
Family-centred care (FCC) is widely used in paediatrics, but is largely untested by rigorous research. As such a critical discourse on its implementation is necessary. Underpinning FCC, and probably the cause of most of the difficulties in its effective implementation, is the importance of effective relationships between the parents of admitted children and health professionals. This paper discusses the relationships between parents and staff and their effect on the delivery of FCC, and is a descriptive review using some historical studies as well as modern research. Aspects of the relationships between parents and staff discussed include communication with doctors, nurse-parent relationships, and the role of partnership with parents in the delivery of care to children and families. These are then examined in relation to FCC and the conclusions support the assertion that if no rigorous research support FCC as a model of care, then it is time to question its widespread use.